Foraging New England : edible wild food and medicinal plants from Maine to the Adirondacks to Long Island Sound - Seymour, Tom (A Falcon guide, 2013)
"From beach peas to serviceberries, hen of the woods to Indian cucumber, ostrich ferns to sea rocket, Foraging New England guides the reader to the edible wild foods and healthful herbs of the Northeast. Helpfully organized by environmental zone, the book is an authoritative guide for nature lovers, outdoorsmen, and gastronomes. "--